Convergent and divergent roles of the glucose-responsive kinase SNF4 in Candida tropicalis. Issue 1 (31st December 2023) - Ke, Cai-Ling; Lew, Shi Qian; Hsieh, Yi; Chang, Szu-Cheng; Lin, Ching-Hsuan
ABSTRACT: The sucrose non-fermenting 1 ( SNF1 ) complex is a heterotrimeric protein kinase complex that is an ortholog of the mammalian AMPK complex and is evolutionally conserved in most eukaryotes. This complex contains a catalytic subunit (Snf1), a regulatory subunit (Snf4) and a scaffolding subunit (Sip1/Sip2/Gal73) in budding yeast. Although the function of AMPK has been well studied in Saccharomyces cerevisiae and Candida albicans, the role of AMPK in Candida tropicalis has never been investigated. In this study, we focused on SNF4 in C. tropicalis as this fungus cannot produce a snf1Δ mutant. We demonstrated that C. tropicalis SNF4 shares similar roles in glucose derepression and is necessary for cell wall integrity and virulence. The expression of both SNF1 and SNF4 was significantly induced when glucose was limited. Furthermore, snf4Δ strains exhibited high sensitivity to many surface-perturbing agents because the strains contained lower levels of glucan, chitin and mannan. Interestingly, in contrast to C. albicans sak1Δ and snf4Δ, C. tropicalis snf4Δ exhibited phenotypes for cell aggregation and pseudohypha production. These data indicate that SNF4 performs convergent and divergent roles in C. tropicalis and possibly other unknown roles in the C. tropicalis SNF1-SNF4 AMPK pathway.